Enhanced Organic Solvent Nanofiltration Membranes with Double Permeance via Laser‐Induced Graphitization of Polybenzimidazole - Seong Heon Kim; Muhammad Ajmal Khan; Kwang Seop Im; Pilgyu Kang; Sang Yong Nam (Advanced Materials Interfaces)
Abstract This study investigates the fabrication of organic solvent nanofiltration (OSN) membranes through laser‐induced graphitization of polybenzimidazole (PBI). Employing a CO2 laser, the polymer is converted into graphene, resulting in controlled submicron‐scale porous 3D structures, a feat not achievable with traditional methods such as chemical crosslinking. The effectiveness of this process hinges on precise adjustments of laser parameters, such as fluence, to attain the ideal graphitization levels. The findings indicate that partial graphitization, as opposed to excessive, is crucial for preserving the membrane's microstructure and enhancing its functional properties. The partially graphitized PBI‐LIG (Polybenzimidazole ‒ Laser‐induced Graphene) membranes achieved up to 94% rejection of Congo red from ethanol, with an ethanol permeance rate of 12.14 LMH bar−1—nearly twice that of standard PBI membranes. Additionally, these membranes showcased outstanding chemical stability and solvent resistance, maintaining over 99% structural integrity and experiencing <1% weight loss after prolonged exposure to various industrial solvents over a week. These results highlight the potential of laser‐graphitized PBI membranes for applications in harsh chemical conditions, paving the way for further optimization of high‐performance OSN membranes. This research advances membrane technology, merging laser engineering with materials science, and contributes to environmental sustainability and industrial efficiency.